TEGANGAN RESIDU KEPING ARESTER SERI - , DEVIA EKA YUNIDA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia is a tropical area with high intensity lightning strike (repeatedly). The voltage produced by lightning by increasing the presence of sensitive loads, lightning can easily worsen the quality of consumer power is generated even if the voltage is relatively low. Lightning strikes can cause excessive voltage along the power lines. Propagation can cause a voltage surge on low voltage systems, especially low voltage can damage the equipment. maintenance and protection against lightning strikes are very necessary for the prevention and countermeasures against such damage. Arrester is a device which is currently intensively used by the public to protect the equipment from lightning strikes. Arrester is a device used to protect the system from lightning with a current danger to earth leaving a certain resistance value so the voltage of the system is not experiencing voltage spikes in the system. This research was conducted through the use of several laboratory-scale testing of major equipment such as high voltage generator, impulse voltage generator, and oscilloscope. Modifications using 220 volt low voltage arrester Merlin Gerin LTD with a maximum current of 6.5 kA as one to four diseri arrester and arrester calculation equations for low voltage circuit series for more than four arrester. From the test results it is known that the characteristics of arrester residual voltage will rise when connected in series. Low voltage arrester can be used for higher voltage requirements by counting the number of arrester. The equation for the required number of series arrester overvoltage surge to cut the y = 0.694x- 0.106R with R2 = 0.989. so that later if needed more than 4 pieces arrester, the residue voltage can be estimated through the formula.